2019
DOI: 10.1038/s41398-018-0360-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide by environment interaction studies of depressive symptoms and psychosocial stress in UK Biobank and Generation Scotland

Abstract: Stress is associated with poorer physical and mental health. To improve our understanding of this link, we performed genome-wide association studies (GWAS) of depressive symptoms and genome-wide by environment interaction studies (GWEIS) of depressive symptoms and stressful life events (SLE) in two UK population-based cohorts (Generation Scotland and UK Biobank). No SNP was individually significant in either GWAS, but gene-based tests identified six genes associated with depressive symptoms in UK Biobank (DCC,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 95 publications
1
81
0
Order By: Relevance
“…Moreover, using pathway analyses in two independent samples (n = 6455, n = 18,759), FDRcorrected associations between depression and a Netrin-1 signaling pathway were identified, comprising SNPs from multiple genes involved in Netrin-1 signaling, including DCC [66]. Additionally, gene-based tests found that depressive symptoms among participants in the UK Biobank (n = 99,057) were associated with six genes, including DCC [67]. Another UK Biobank (n = 122,935) gene-based analysis found associations between suicidality and five genes, including DCC [68].…”
Section: Depressionmentioning
confidence: 99%
“…Moreover, using pathway analyses in two independent samples (n = 6455, n = 18,759), FDRcorrected associations between depression and a Netrin-1 signaling pathway were identified, comprising SNPs from multiple genes involved in Netrin-1 signaling, including DCC [66]. Additionally, gene-based tests found that depressive symptoms among participants in the UK Biobank (n = 99,057) were associated with six genes, including DCC [67]. Another UK Biobank (n = 122,935) gene-based analysis found associations between suicidality and five genes, including DCC [68].…”
Section: Depressionmentioning
confidence: 99%
“…However, the analytical modelling used in GWAS and whole-genome approaches usually assumes that there is no genotype-environment interaction (GxE), which can be often violated against the true genetic architecture of complex traits. Indeed, interaction is fundamental in biology and there has been increasing interest in estimating GxE, using genome-wide SNPs [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, there was the likelihood of systematic inflation on the significance of interaction. To correct heteroscedasticity on the analysis, methods that use the robust standard error ( SE ) were proposed (Voorman et al, 2011); there was some evidence when those methods were used (Almli et al, 2014; Arnau‐Soler et al, 2019). However, we could not correct the systematic inflation on our data set even when using the robust SE approach as well as adjusting the principle component for population stratification (data not shown).…”
Section: Discussionmentioning
confidence: 99%